Little needle-scalpel for piriformis syndrome: A protocol for systematic review and meta-analysis. Issue 12 (26th March 2021) - Zhu, Qingyuan; Zhu, Siyuan; Xiong, Jun; Lu, Lunbin; Chen, Jun; Zhong, Zhiying; Tang, Genhua
Abstract: Background: Piriformis syndrome (PS) is a condition in which the sciatic nerve is compressed when passing through the inferior mouth of the piriformis muscle, mainly caused by pain in one hip and leg. In severe cases, patients may experience severe buttock and lower limb pain, discomfort, difficulty walking, and claudication. It is estimated that the annual incidence of low back pain and sciatica is about 40 million cases, and the annual incidence of piriformis syndrome is about 2.4 million cases. The aim of this systematic review is to assess the effectiveness and safety of Little needle-scalpel therapy for Piriformis syndrome. Methods: Two reviewers will electronically search the following databases: the Cochrane Central Register of Controlled Trials (CENTRAL); PubMed; EMBASE; China National Knowledge Infrastructure (CNKI); Chinese Biomedical Literature Database (CBM); Chinese Scientific Journal Database (VIP database); and Wan-Fang Database from the inception, without restriction of publication status and languages. Additional searching including researches in progress, the reference lists, and the citation lists of identified publications. Study selection, data extraction, and assessment of study quality will be performed independently by 2 reviewers. If it is appropriate for a meta-analysis, RevMan 5.4 statistical software will be used; otherwise, a descriptive analysis will be conducted. Data will be synthesized by either the fixed-effects or random-effects model according to a heterogeneity test. The results will be presented as risk ratio (RR) with 95% confidence intervals (CIs) for dichotomous data and weight mean difference (WMD) or standard mean difference (SMD) 95% CIs for continuous data. Results: This study will provide a comprehensive review of the available evidence for the treatment of Little needle-scalpel with piriformis syndrome. Conclusions: The conclusions of our study will provide an evidence to judge whether Little needle-scalpel is an effective and safe intervention for patients with piriformis syndrome. Ethics and dissemination: This systematic review will be disseminated in a peer-reviewed journal or presented at relevant conferences. It is not necessary for a formal ethical approval because the data are not individualized. Trial registration number: INPLASY2020110092.